IL-10 Producing B Cells Dampen Protective T Cell Response and Allow Chlamydia muridarum Infection of the Male Genital Tract - Sanchez, Leonardo R.; Godoy, Gloria J.; Gorosito Serrán, Melisa; Breser, Maria L.; Fiocca Vernengo, Facundo; Engel, Pablo; Motrich, Ruben D.; Gruppi, Adriana; Rivero, Virginia E. (Frontiers in Immunology, 2019)
A significant proportion of individuals develop chronic, persistent and recurrent genital tract infections with Chlamydia trachomatis, which has been attributed to the numerous strategies that the bacterium uses to subvert host immune responses. Animal chlamydia models have demonstrated that protective immune response is mediated by CD4+ Th1 cytokine responses. Herein, we demonstrate that early after infecting the male genital tract, C. muridarum triggers the production of IL-10 by splenic and lymph node cells. In addition, C. muridarum triggers IL-6 and TNFα secretion. Data obtained from in vitro and in vivo experiments revealed B cells as the major IL-10 contributors. Indeed, purified B cells produced high amounts of IL-10 and also exhibited enhanced expression of inhibitory molecules such as CD39, PD-L1 and PD1 after C. muridarum stimulation. In vitro experiments performed with sorted cell subsets revealed that Marginal Zone B cells were the main IL-10 producers. In vitro and in vivo studies using TLR-deficient mice indicated that TLR4 signaling pathway was essential for IL-10 production. In addition, in vivo treatments to neutralize IL-10 or deplete B cells indicated that IL-10 and B cells played a significant role in delaying bacterial clearance ability. Moreover, the latter was confirmed by adoptive cell transfer experiments in which the absence of IL-10-producing B cells conferred the host a greater capability to induce Th1 responses and clear the infection. Interestingly, NOD mice, which were the least efficient in clearing the infection, presented much more Marginal Zone B counts and also enhanced TLR4 expression on Marginal Zone B cells when compared to B6 and BALB/c mice. Besides, treatment with antibodies that selectively deplete Marginal Zone B cells rendered mice more capable of inducing enhanced IFN responses and clearing the infection. Our findings suggest that B cells play a detrimental role in C. muridarum infection and that activation by innate receptors like TLR4 and IL-10 production by these cells could be used by Chlamydia spp. as a strategy to modulate the immune response establishing chronic infections in susceptible hosts.